Hi there!
Let's solve this equation step by step!
6f + 9g = 3g + f
To solve for f, we need to bring all the terms in the equation with an f in it to the left, and all the other terms (with a g) to the right.
First subtract f from both sides.
5f + 9g = 3g
Now subtract 9g from both sides.
5f = -6g
And finally divide both sides by 5.
f = (-6/5)g
Hence, your answer;
![f = - (6)/(5) g](https://img.qammunity.org/2019/formulas/mathematics/high-school/pka5ukqrgxepd0bac4cwk499zd7188dncq.png)
~ Hope this helps you!